Ejercicios docentes de Mies van der Rohe: «Una residencia de estudiantes», por David Tamminga = Mies van der Rohe’s teaching exercises: «Students residence» by David Tamminga - García Requejo, Zaida (Cuaderno de Notas, 2023)
AbstractMies van der Rohe’s teaching is an inseparable part of his career as an architect. Upon his arrival in the United States, his classes became a laboratory of ideas in which he tested solutions to problems he faced in his office. This research deals with a comparative analysis of the architectural principles proposed by Mies for the university campus of the Illinois Institute of Technology (IIT) and the academic work carried out by graduate students that solves the same functional topic. First, an analysis of the general approaches of the campus project is addressed to, later, focus the study on the buildings intended for student housing. Thus, student David Tamminga’s final master’s project is analyzed in parallel to the three residential blocks designed by Mies for the IIT, seeking to establish connections and influences between his teachings and his architecture.ResumenLa labor docente de Mies van der Rohe forma parte indisoluble de su trayectoria como arquitecto. A su llegada a los Estados Unidos, sus clases se convirtieron en un laboratorio de ideas en el que testar soluciones a problemas a los que se enfrentaba en su oficina. Esta investigación aborda un análisis comparativo de los principios arquitectónicos planteados por Mies para el campus universitario del Illinois Institute of Technology (IIT) y el trabajo académico llevado a cabo por alumnos de posgrado que resuelve la misma temática funcional. Primero, se aborda un análisis de los planteamientos generales del proyecto del campus para, posteriormente, centrar en el estudio en las edificaciones destinadas a residencia de estudiantes. Así el proyecto fin de máster del estudiante David Tamminga se analiza en paralelo a los tres bloques residenciales proyectados por Mies para el IIT, buscando establecer conexiones e influencias entre sus enseñanzas y su arquitectura.